2022
DOI: 10.1101/2022.08.29.505667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wild grass isolates of Magnaporthe (Syn. Pyricularia) spp. from Germany can cause blast disease on cereal crops

Abstract: Pathogens that cause destructive crop diseases often infect wild host plants. However, surveys of major plant pathogens tend to be skewed towards cultivated crops and often neglect the wild hosts. Here, we report an emerging disease threat generated by the blast fungus Magnaporthe (Syn. Pyricularia) spp. in central Europe. We found that this notoriously devastating plant pathogen infects the wild grasses foxtail millet (Setaria spp.) and crabgrass (Digitaria spp.) in south-western Germany, a region previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 69 publications
0
16
0
1
Order By: Relevance
“…We designed a KASP marker for the Rwt4-1B homoeologue (Supplementary Tables 7 and 9) that, along with those for Rwt3 and Rwt4-1D, should enable wheat breeders to ensure that cultivars maintain host-specificity barriers. It was recently shown that, even though the pandemic clonal lineages tend to dominate Triticum pathotypes, sexual recombination between Triticum and non-Triticum pathotypes is possible and can raise the adaptive potential of Triticum pathotypes in the absence of host-specificity barriers 22,23 . This suggests that PWT4, which is naturally found in Lolium pathotypes isolated from Avena but not in Triticum pathotypes 6 , can potentially be gained by Triticum pathotypes through sexual recombination.…”
Section: Brief Communicationmentioning
confidence: 99%
“…We designed a KASP marker for the Rwt4-1B homoeologue (Supplementary Tables 7 and 9) that, along with those for Rwt3 and Rwt4-1D, should enable wheat breeders to ensure that cultivars maintain host-specificity barriers. It was recently shown that, even though the pandemic clonal lineages tend to dominate Triticum pathotypes, sexual recombination between Triticum and non-Triticum pathotypes is possible and can raise the adaptive potential of Triticum pathotypes in the absence of host-specificity barriers 22,23 . This suggests that PWT4, which is naturally found in Lolium pathotypes isolated from Avena but not in Triticum pathotypes 6 , can potentially be gained by Triticum pathotypes through sexual recombination.…”
Section: Brief Communicationmentioning
confidence: 99%
“…The filamentous ascomycete fungus M . oryzae causes blast disease in cereal crops, such as rice, wheat ( Triticum aestivum ), and foxtail millet ( Setaria italica ) [ 6 8 ]. M .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the M. oryzae-host pathosystem benefited from examining gene-for-gene interactions. The filamentous ascomycete fungus M. oryzae causes blast disease in cereal crops, such as rice, wheat (Triticum aestivum), and foxtail millet (Setaria italica) [6][7][8]. M. oryzae consists of genetic subgroups that have infection specificities for particular host genera [7].…”
Section: Introductionmentioning
confidence: 99%
“…Both acreage and production of wheat had been increasing until a sudden massive outbreak of wheat blast occurred in 2016 [5]. In February 2016, wheat blast disease was spotted in Bangladesh for the first time in a country outside of South America that devastated more than 15,000 hectares of wheat with up to 100% yield losses [6], and very recently, it was also identified in Zambia [7] and potentially threatens wheat production in Europe [8]. After the epidemic of this pathogen in Bangladesh, it was rapidly identified by field pathogenomics and open data sharing against the aggressive clonal population of a South American lineage of M. oryzae (anamorph Pyricularia oryzae) Triticum (MoT) pathotype [6].…”
Section: Introductionmentioning
confidence: 99%